Discriminação de méis de abelhas sem ferrão da região Amazônica baseada em análises de GC-MS e quimiométricas - França, Rebeca dos Santos (Brasil, 2024)
Apiculture and meliponiculture play a fundamental role in the subsistence of local communities and in the conservation of biodiversity in the Amazon Region. However, the diversity of stingless bees (SB) in this region results in a wide variety of honeys with a unique flavor, aroma and chemical composition. The distinction between these honeys is crucial both for the appreciation of local products and for authenticity and traceability in the market. In this context, gas chromatography coupled to mass spectrometry (GC-MS) in conjunction with chemometric tools has proven to be a valuable approach for the discrimination and survey of chemical markers in diverse matrices. Therefore, the present work aimed to discriminate SB honeys from the Amazon Region by GC-MS and chemometric analyses. For this, 22 samples of SB honey were obtained from meliponarias in the states of Amazonas and Para. The lipid extracts from the samples were analyzed in a GC-MS system. The chemical profiles obtained were subjected to principal component analysis (PCA) and hierarchical cluster analysis (HCA). 39 peaks were detected, with retention indices varying between 1070 and 3427, of which 18 were identified as substances from different chemical classes already reported in honeys. From PCA and HCA, it was observed the separation of honey samples into two groups, with group I formed by samples from Amazonas, and group II, by samples from Pará. Two compounds derived from (3-methyl-butyl)benzene and scopoletin were identified as potential chemical markers for group I, which may indicate the presence of promising biological properties in these samples. 5-hydroxymethylfurfural (HMF), used to evaluate the quality of honeys, was responsible for the segregation of group II, requiring further investigation into its concentration in these honeys, in order to guarantee food safety for consumers. Sherry lactone, a compound not reported in Brazilian honeys, was identified as a distinctive chemical marker in one of the honey samples from Pará. Thus, this work highlighted the similarities in the chemical composition of honey samples from ASF according to the region, in addition to the possible biological properties that add value to this beekeeping product.